2020
DOI: 10.1038/s41598-020-63899-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel specific PERK activator reduces toxicity and extends survival in Huntington's disease models

Abstract: One of the pathways of the unfolded protein response, initiated by PKR-like endoplasmic reticulum kinase (PERK), is key to neuronal homeostasis in neurodegenerative diseases. PERK pathway activation is usually accomplished by inhibiting eIF2α-P dephosphorylation, after its phosphorylation by PERK. Less tried is an approach involving direct PERK activation without compromising long-term recovery of eIF2α function by dephosphorylation. Here we show major improvement in cellular (STHdh Q111/111 ) and mouse (R6/2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 56 publications
6
71
0
Order By: Relevance
“…BTdCPU and other N,N′ diaryl urea derivatives are specific HRI activators (figure, s.2), which are also con sidered as promising antitumor drugs [269]. CCT020312 and MK 28 are pharmacological activators of PERK (fig ure, s.1) and can be potentially used in the treatment of neuropathies [270,271]. Specific activators of GCN2 kinase ( figure, s.3) have not yet been sufficiently studied; however, recent screening identified two candidatessmall molecules dabrafenib and MK1775 [264].…”
Section: Inhibitors Of Signaling Pathways Involved In Translational Cmentioning
confidence: 99%
“…BTdCPU and other N,N′ diaryl urea derivatives are specific HRI activators (figure, s.2), which are also con sidered as promising antitumor drugs [269]. CCT020312 and MK 28 are pharmacological activators of PERK (fig ure, s.1) and can be potentially used in the treatment of neuropathies [270,271]. Specific activators of GCN2 kinase ( figure, s.3) have not yet been sufficiently studied; however, recent screening identified two candidatessmall molecules dabrafenib and MK1775 [264].…”
Section: Inhibitors Of Signaling Pathways Involved In Translational Cmentioning
confidence: 99%
“…We also evaluated the effect of another PERK activator, CCT020312,[ 36 , 37 ] on the 22DS group phenotypes. Similar to salubrinal, CCT020312 ameliorated cell vulnerability to ER stress and F-actin dynamics in the 22DS group with the upregulation of PERK activity (Supplementary Figures 11).…”
Section: Resultsmentioning
confidence: 99%
“…In HD condition it has been upregulated. In the follow-up study, the Lederkremer group very recently showed PERK activator MK-28 can successfully reduce toxicity and extend survival in Huntington’s disease models [ 232 ].…”
Section: Mam Proteins (Ire1 and Perk) In Neuronal Diseasementioning
confidence: 99%